2022
DOI: 10.3390/v14071478
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 Induces Formation of Virus-p62-PML Hybrid Bodies to Enable Infection

Abstract: Human papillomaviruses (HPVs) inflict a significant burden on the human population. The clinical manifestations caused by high-risk HPV types are cancers at anogenital sites, including cervical cancer, as well as head and neck cancers. Host cell defense mechanisms such as autophagy are initiated upon HPV entry. At the same time, the virus modulates cellular antiviral processes and structures such as promyelocytic leukemia nuclear bodies (PML NBs) to enable infection. Here, we uncover the autophagy adaptor p62,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…The GTPase‐activating protein folliculin safeguards incoming HPV virions from lysosomal degradation, 41 similar to the role of coat protein complex I 42 . The virus remains within in the Golgi until cell cycle progression into mitosis, when the breakdown of the nuclear membrane facilitates the accumulation of viral DNA at promyelocytic leukemia nuclear bodies, where is the site of viral transcription and replication 31,37,43 . However, the process of intranuclear delivery and the cellular proteins involved in these steps remain uncertain.…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The GTPase‐activating protein folliculin safeguards incoming HPV virions from lysosomal degradation, 41 similar to the role of coat protein complex I 42 . The virus remains within in the Golgi until cell cycle progression into mitosis, when the breakdown of the nuclear membrane facilitates the accumulation of viral DNA at promyelocytic leukemia nuclear bodies, where is the site of viral transcription and replication 31,37,43 . However, the process of intranuclear delivery and the cellular proteins involved in these steps remain uncertain.…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“…Rizzato's study demonstrated that the CDK1 and PLK1 sequentially phosphorylate the chromosome binding region of L2 to regulate the delivery of HPV viral DNA to mitotic chromatin during mitosis 44 . Additionally, the autophagy adaptor p62 may also have involvement in the nuclear delivery process 43 . Numerous studies have investigated the mechanism of HPV entry.…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Daxx downregulation negatively affected the expression of early genes and, consequently, viral genome replication. Finally, Schweiger et al [ 149 ] recently showed that the autophagy receptor p62 binds to subviral particles in endosomes and accompanies them to the nucleus, where hybrid p62-subviral particle-PML assemblies are detected. The authors suggested that the interaction between subviral particles and p62 exerts a protective effect on the viral genome.…”
Section: Small and Medium Size Dna Viruses And Their Interactions Wit...mentioning
confidence: 99%
“…The authors suggested that the interaction between subviral particles and p62 exerts a protective effect on the viral genome. p62 depletion resulted in the degradation of L2 and a decrease in the expression of the reporter gene carried by the pseudovirions [ 149 ].…”
Section: Small and Medium Size Dna Viruses And Their Interactions Wit...mentioning
confidence: 99%